Scalable process development of NK and CAR-NK expansion in a closed bioreactor - Wang, Xuening; Byrne, Maeve Elizabeth; Liu, Chang; Ma, Minh Tuyet; Liu, Dongfang (Frontiers in Immunology, 2024)
Production of large amounts of functional NK and CAR-NK cells represents one of the bottlenecks for NK-based immunotherapy. In this study, we developed a large-scale, reliable, and practicable NK and CAR-NK production using G-Rex 100M bioreactors, which depend on a gas-permeable membrane technology. This system holds large volumes of medium with enhanced oxygen delivery, creating conditions conducive to large-scale PBNK and CAR-NK expansions for cancer therapy. Both peripheral blood NK cells (PBNKs) and CAR-NKs expanded in these bioreactors retained similar immunophenotypes and exhibited comparable cytotoxicity towards hepatocellular carcinoma (HCC) cells akin to that of NK and CAR-NK cells expanded in G-Rex 6 well bioreactors. Importantly, cryopreservation minimally affected the cytotoxicity of NK cells expanded using the G-Rex 100M bioreactors, establishing a robust platform for scaled-up NK and CAR-NK cell production. This method is promising for the development of “off-the-shelf” NK cells, supporting the future clinical implementation of NK cell immunotherapy.